AT THE FOREFRONT OF EPIDEMIOLOGY (THE 85TH ANNIVERSARY OF THE DEPARTMENT OF EPIDEMIOLOGY AND EVIDENCE-BASED MEDICINE SECHENOV FIRST MOSCOW STATE MEDICAL UNIVERSITY) - N. I. Briko; A. Ya. Mindlina; R. V. Polibin; T. V. Sokolova; N. N. Tsapkova (Сеченовский вестник, 2022)
The article presents the paradigm of modern training in epidemiology: technologies and methods used by the Department of Epidemiology and Evidence-based Medicine. The contemporary training process requires various educational technologies, including interactive and computer technologies. The article dwells upon the ﬁelds of the Departments scientiﬁc activities including the Students’ scientiﬁc circle. The article demonstrates that the epidimiologists training should be focused on professional competences necessary both in Rospotrebnadzor and in the Ministry of Health.